Mulligan Versus Conventional Neurodynamic Mobilization in Patients with Cervical Radiculopathy - A Randomized Controlled Trial (International Journal of Physiotherapy, 2021)
Background: Cervical radiculopathy is a type of neck disorder. Here a nerve root in the cervical spine becomes inflamed or impinged, resulting in neurological functions. They may radiate anywhere from the neck into the shoulder, arm, hand, or fingers. While the clinical diagnostic tests of cervical radiculopathy are well established in the literature, studies finding the usefulness of rehabilitation interventions are few. Therefore, the objective of the present study was to compare the effectiveness of mulligan mobilization versus conventional neurodynamics in cervical radiculopathy.Methods: 30 subjects with age group 30 – 55 years who were clinically diagnosed with cervical radiculopathy &having one Upper Limb Tension Test positive were included in the study. They were randomized to Mulligan Neurodynamic Mobilization Group or Conventional Neurodynamics Group. The treatment sessions (3 repetitions, 3 sets) in both groups lasted for 5 consecutive days. Outcomes were measured using the Numerical Pain Rating Scale(NPRS) for pain, Cervical ranges, and patient-specific functional scale (PSFS) for disability.Results: Wilcoxon test was used for within-group whereas the Mann-Whitney test was used for between-group comparisons. The test revealed similar improvements in pain and disability in both groups (p>0.05); however, the Mulligan Neurodynamic Mobilization Group showed better results in terms of cervical ranges (p